The Impact of Structured Aerobic Exercise on Sleep Quality and Emotional Regulation Capacity: A Systematic Literature Review - Siti Rodiah; Raihan Veryadi; Adam Khalifah Pujiantoro; M. Arif Setiawan; Zaky Mubarak (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2026)
The purpose of the study. This systematic literature review aims to analyze and synthesize the evidence on the effects of structured aerobic exercise on sleep quality and emotional regulation capacity in healthy adults and clinical populations. Materials and methods. A comprehensive electronic search was conducted in PubMed, Scopus, Web of Science, and Google Scholar, covering publications from January 2015 to December 2024. Studies were selected based on pre-defined inclusion and exclusion criteria, focusing on peer-reviewed articles that investigated structured aerobic exercise interventions and reported sleep quality outcomes (assessed via Pittsburgh Sleep Quality Index, PSQI) and/or emotional regulation outcomes (assessed via the Emotion Regulation Questionnaire, ERQ). Data extraction and quality appraisal followed the PRISMA 2020 guidelines. Results. A total of 12 studies met the inclusion criteria and were included in the final synthesis. Structured aerobic exercise with a frequency of 3–5 sessions per week, 30–60 minutes per session, and moderate-to-vigorous intensity demonstrated significant improvements in sleep efficiency, reduction in sleep latency, and enhancement of slow-wave sleep duration. Concurrently, consistent aerobic training improved cognitive reappraisal strategies and reduced emotional suppression, mediated by increased prefrontal cortex activity and elevated brain-derived neurotrophic factor (BDNF) levels. Conclusions. Structured aerobic exercise exerts dual benefits on psychophysiological health by improving both sleep quality and emotional regulation through neurobiological and psychoneuroendocrine mechanisms. It is recommended as a viable non-pharmacological intervention in clinical and community health settings.